Life Cycle Assessment (LCA) of the Impact on the Environment of a Cosmetic Cream with Gold Nanoparticles and Hydroxylated Fullerene Ingredients - Rebeka Rudolf; Peter Majerič; Zorka Novak Pintarič; Andrej Horvat; Damjan Krajnc (Applied Sciences)
This review provides a comprehensive Life Cycle Assessment (LCA) of a cosmetic cream to assess the environmental impacts throughout its entire life cycle, from raw material extraction to disposal, using the methodology according to international standards. The LCA was performed using the OpenLCA 2.0.1 software, with data from the Ecoinvent 3.8 database and relevant literature. The assessment focused on multiple impact categories, including climate change, acidification, eutrophication (freshwater, marine and terrestrial), ecotoxicity (freshwater), human toxicity (cancer and non-cancer), ionizing radiation, land use, ozone depletion, photochemical ozone formation, resource use (fossils, minerals and metals), and water use. The LCA of a cosmetic cream containing gold nanoparticles revealed significant environmental impacts across critical categories. The total climate change potential was 2596.95 kg CO2 eq., driven primarily by nanoparticle synthesis (60.7%) and electricity use (31.9%). Eutrophication of freshwater had the highest normalized result (3.000), with nanoparticle synthesis contributing heavily, indicating the need for improved wastewater treatment. The resource use (minerals and metals) scored 1.856, while the freshwater ecotoxicity reached 80,317.23 CTUe, both driven by the nanoparticle production. The human toxicity potentials were 1.39 × 10−6 CTUh (cancer) and 7.45 × 10−5 CTUh (non-cancer), linked to emissions from synthesis and energy use. The LCA of the cosmetic cream revealed several critical areas of environmental impact. The most significant impacts are associated with gold nanoparticle synthesis and electricity use. Addressing these impacts through optimized synthesis processes, improved energy efficiency, and alternative materials can enhance the product’s sustainability profile significantly.